2004
DOI: 10.1093/nar/gkh988
|View full text |Cite
|
Sign up to set email alerts
|

Distributions of Z-DNA and nuclear factor I in human chromosome 22: a model for coupled transcriptional regulation

Abstract: An analysis of the human chromosome 22 genomic sequence shows that both Z-DNA forming regions (ZDRs) and promoter sites for nuclear factor-I (NFI) are correlated with the locations of known and predicted genes across the chromosome and accumulate around the transcriptional start sites of the known genes. Thus, the occurrence of Z-DNA across human genomic sequences mirrors that of a known eukaryotic transcription factor. In addition, 43 of the 383 fully annotated chromosomal genes have ZDRs within 2 nucleosomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
82
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 27 publications
9
82
1
1
Order By: Relevance
“…It has been demonstrated that the E3L N-terminal domain binding to Z-DNA is necessary for pathogenicity in mice (8). Z-DNA-forming sequences are found near the transcription start site of many human genes (14), and negative supercoiling generated behind a moving polymerase during transcription (15) stabilizes Z-DNA formation. Z-DNA formation has been detected in the promoter region of actively transcribed genes in mammalian cells (16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the E3L N-terminal domain binding to Z-DNA is necessary for pathogenicity in mice (8). Z-DNA-forming sequences are found near the transcription start site of many human genes (14), and negative supercoiling generated behind a moving polymerase during transcription (15) stabilizes Z-DNA formation. Z-DNA formation has been detected in the promoter region of actively transcribed genes in mammalian cells (16).…”
Section: Resultsmentioning
confidence: 99%
“…Because Z-DNA cannot form nucleosomes (30), it leaves a nucleosome-free region near the transcription start site, allowing transcription factors to be recruited, so that transcription ensues. Because most human genes have Z-DNA-forming sequences near the transcription start site (14), it is possible that E3L binding to such sequences up-regulates transcription. Further experiments are clearly necessary.…”
Section: Resultsmentioning
confidence: 99%
“…The authors suggested that Z-DNA upstream of the nuclear factor-1 binding site helped to maintain the gene in its activated, nucleosome-free state (nucleosomes do not bind to the very rigid Z-DNA form (Ausio et al, 1987)). In support of its potential role in the regulation of eukaryotic genes, we have found that Z-forming sequences accumulate near the transcription start site of genes in humans and other eukaryotes (Khuu et al, 2007;Schroth et al, 1992), and that ~80% of the genes in human chromosome 22 have at least one Z-DNA sequence in the vicinity of their transcription start sites (Champ et al, 2004). The discovery of protein domains having very high specificity for Z-DNA (Rich and Zhang, 2003), in some cases with nanomolar K D 's, have suggested additional functions that include, for example, RNA editing and gene transactivation.…”
Section: Z-dnamentioning
confidence: 83%
“…The potential to form a Z-DNA structure also correlates with regions of active transcription. By analysis of the human chromosome 22 genomic sequence, Champ et al (2004) showed that both Z-DNAforming regions and promoter sites for nuclear factor-I correlate with the location of known and predicted genes across the chromosome and accumulate around the transcriptional start sites of the known gene. Therefore, we supposed that the insertion of the element influenced the twist gene downstream and further resulted in the mutant phenotype.…”
Section: Sequence Cloning and Nucleotide Analysismentioning
confidence: 99%